Knowledge bases of intelligent systems - Nikitina, L. O. (My University, 2023)
This tutorial gives an introduction to key concepts in Knowledge Based Engineering. The tutorial examines issues related to the organization and construction of knowledge base, which is a component of intelligent system. The place of the knowledge base in the intelligent computer system is explained. Features of collection, storage, search and issuance of knowledge are highlighted. The process of building and maintaining intelligent problem-solving systems that use (symbolic) AI methods is presented. The topics include knowledge representation and reasoning, knowledge acquisition, knowledge synthesis and knowledge evolution. The material of this tutorial is recommended for students majoring in "Computer Science".
Keywords: textbook; the types of artificial intelligence; a process of knowledge engineering; thinking rationally; predicate logic; semantic networks; scripts; ontologies; types of frames